Peningkatan Hasil Belajar Peserta Didik Dengan Menggunakan Model Problem Baside Learning(PBL) PadaPembelajaran Tematik Terpadu Di Kelas IV SD - Silvia Yerika Putri; Farida S (Universitas Negeri Padang, 2022)
The problem in this research is motivated by learning that is not yet centered on students and also student learning outcomes that are not as expected.In this integrated thematic learning, the teacher has not introduced students to real problems that are close to the students' environment. This study aims to describe the application of the Problem Based Learning model to improve learning outcomes in integrated thematic learning for class IV SDN 03 Pancung Tebal Pesisir Selatan Regency. The type of research used in this research is CAR with qualitative and quantitative approaches. The results showed an increase in integrated thematic learning outcomes from cycle I to cycle II, namely: (1) The average assessment of lesson plans in the first cycle was 80.55% (B), the second cycle increased to 94.44%. (2) The average assessment of teacher aspects in the first cycle was 82.14% (B), the second cycle increased to 96.42% (SB). (3) The average assessment of the aspects of students in the first cycle is 82.14% (B), the second cycle increases to 96.42% (SB). (4) The average assessment of knowledge and skills in the first cycle was 79.56 (B), the second cycle increased to 87.09 (SB).